ATP Bioluminometers Analysis on the Surfaces of Removable Orthodontic Aligners after the Use of Different Cleaning Methods - Luca Levrini; Alessandro Mangano; Silvia Margherini; Camilla Tenconi; Davide Vigetti; Raffaele Muollo; Gian Marco Abbate (Hindawi Limited, 2016)
Purpose. The aim was to quantify the bacteria concentration on the surface of orthodontic clear aligners using three different cleaning methods. Furthermore the objective was to validate the efficacy of the bioluminometer in assessing the bacteria concentration. Materials and Methods. Twenty subjects (six males and fourteen females) undergoing orthodontic therapy with clear aligners (Invisalign® Align Technology, Santa Clara, California) were enrolled in this study. The observation time was of six weeks. The patients were instructed to use different cleaning methods (water, brushing with toothpaste, and brushing with toothpaste and use of sodium carbonate and sulphate tablet). At the end of each phase a microbiological analysis was performed using the bioluminometer. Results. The highest bacteria concentration was found on aligners cleaned using only water (583 relative light units); a value of 189 relative light units was found on aligners cleaned with brushing and toothpaste. The lowest bacteria concentration was recorded on aligners cleaned with brushing and toothpaste and the use of sodium carbonate and sulfate tablet. Conclusions. The mechanical removal of the bacterial biofilm proved to be effective with brushing and toothpaste. The best results in terms of bacteria concentration were achieved adding the use of sodium carbonate and sulfate tablet.